Reproducibility in interlaboratory impact sound insulation measurements - António Pedro O. Carvalho (2006)
This paper presents the results of an interlaboratory comparison test concerning the impact sound insulation for a concrete slab floor to determine the reproducibility for the weighted normalized impact sound pressure level Ln,w and for all the involved main parameters (reverberation time and impact normalized sound pressure level, at the receiving room and for each 100 to 3150 Hz frequency band). The reproducibility of the parameter Ln,w was calculated to be 2.3 dB with the individual laboratories performance z-scores varying up to 1.8. The laboratories z-scores for the reverberation time values were up to 2.4 (with a range of values of 4 s for the RT results at the frequency bands of 100 and 125 Hz). The RT values reproducibility was calculated to be from 0.1 s in the higher frequency bands to about 3 s in the very low frequency bands. The laboratories z-scores for the normalized sound pressure level (Ln) were up to 2.6 (with a range of values of 8 to 12 dB in the frequency bands of 100 to 160 Hz). The reproducibility for these values was calculated to be from 1.8 to 6.3 dB. The measurement process is analyzed and the main conclusions are commented.